How heat stress (continuous or cyclical) interferes with nutrient digestibility, energy and nitrogen balances and performance in broilers - Souza, Lilian Francisco Arantes de [UNESP]; Espinha, Lívia Pegoraro [UNESP]; Almeida, Eduardo Alves de [UNESP]; Lunedo, Raquel [UNESP]; Furlan, Renato Luís [UNESP]; Macari, Marcos [UNESP] (Elsevier, 2016)
The effect of continuous and cyclical heat stress on broiler growth performance, nutrient digestibility, energy and nitrogen balances was investigated. Four hundred and fifty, 21-day-old, Cobb male broilers were raised in battery cages in five treatments: 22C/AL (continuous 22 °C, ad libitum feed consumption); 32C/AL (continuous 32 °C, ad libitum feed consumption); 22C/PF32C (continuous 22 °C, pair-fed on the daily feed intake of 32C/AL); CY/AL (cyclical – 32 °C for 8 h and 25 °C for 12 h, ad libitum feed consumption); 22C/PFCY (continuous 22 °C, pair-fed on the daily feed intake of CY/AL). Between 39 and 42 days of age, dry matter, crude protein, crude fat and AMEn were analyzed in the diets and excreta to determine nutrient digestibility. Energy and nitrogen balances were evaluated through comparative slaughter (21 and 42 days of age). Growth performance was significantly lower in broilers exposed to either continuous or cyclical heat stress. However, the cyclical heat stress had a lower effect on feed intake and weight gain and no effect on the feed conversion rate. Nutrient digestibility was only influenced by continuous heat exposure, decreasing dry matter (3.9%) and protein digestibility (9.7%) in comparison to control birds. Broilers exposed to continuous heat stress increased metabolizable energy intake (20.3%) and heat production (35.5%), and decreased energy retention (20.9%) and energy efficiency (32.4%) in relation to control ones. Nitrogen intake and nitrogen retention were reduced by both forms of heat exposure, in comparison to control, but more strongly under continuous heat. Nitrogen retention was reduced by 50.4% and 20.4%, for continuous or cyclical heat stress, respectively. Nitrogen efficiency was reduced only by the continuous heat exposure (33.1%). These results revealed important differences between the effects of a continuous or a cyclical heat exposure in broiler chickens for digestibility, performance and energy and nitrogen balances.
Keywords: Continuous heat stress; Cyclical heat stress; Heat production; Nitrogen efficiency; Nutrient digestibility; Pair-feeding